Smartphone addiction and sleep quality among nursing students in Meknes, Morocco: A cross-sectional study - El Haddaouy, Abdelhadi; Miyah, Youssef; Benjelloun, Mohammed; Mengad, Aziz; Blaak, Hicham; Iziki, Hayat; El Omari, Fatima (Belitung Raya Publisher - Belitung Raya Foundation, 2025)
Background: Smartphone addiction and poor sleep quality are prevalent health concerns that negatively impact students’ physical and mental well-being, which could affect their academic performance. However, research on this subject in Morocco remains limited. Objective: This study aimed to examine the impact of smartphone addiction on sleep quality and identify risk factors that moderate this relationship among nursing students. Methods: This cross-sectional study was conducted from March to July 2023, involving 451 nursing students aged 17 to 23 at the Higher Institute of Nursing Professions and Health Techniques in Meknes, Morocco. Participants completed the Mobile Phone-Related Sleep Risk Factors Questionnaire (MRSRF), the Smartphone Addiction Scale–Short Version (SAS-SV), and the Pittsburgh Sleep Quality Index (PSQI). Binary logistic regression (BLR), Receiver Operating Characteristic (ROC) curves, and Area Under Curve (AUC) analyses were used to assess the impact of smartphone addiction on sleep quality and to identify moderating risk factors. Results: The study found that 81.23% of nursing students experienced smartphone addiction, and 86.47% reported poor sleep quality. Sleep quality was significantly correlated with smartphone addiction (β = 0.174; p <0.001), use before bedtime (β = 1.018; p = 0.030), and duration of use after lights-off (β = 0.768; p = 0.047). Logistic regression analysis indicated that smartphone addiction (AUC = 0.872; p <0.001) and duration of use after lights-off (AUC = 0.668; p <0.001) were significant predictors of sleep quality. Conclusion: This study found a significant correlation between smartphone addiction and poor sleep quality, as well as a negative impact of using smartphones in bed for more than 30 minutes after lights off. Nursing students with higher smartphone addiction levels, who use their devices for extended periods without blue light filters, are more likely to experience poor sleep quality. Addressing these challenges requires an integrated, multidisciplinary approach involving healthcare professionals, educators, and community stakeholders. Health promotion programs integrated into student curricula could help reduce smartphone addiction and encourage healthier sleep hygiene practices.